Petrology and Genesis of the Bhainskati Iron Ore Deposit of Palpa District, Western Nepal - Poudel, Lalu; Devkota, Sujan (Tribhuvan University Journal, 2013)
The Bhainskati Formation of the Tansen Group in Palpa area is known for hematite iron ore deposit for long time. A prominent band of hematite of about 1-2 km thickness extending >5 km was identified in the upper part of the Bhainskati Formation in the present study and the band is repeated three times in the area by folding and faulting. Petrographic study shows that it is oolitic ironstone of sedimentary shallow marine origin. Main minerals in the band are hematite, goethite, quartz, calcite, siderite and albite. Hematite content varies considerably among samples and occurs mainly as oolite and cement. The Bhainskati ironstone with its ferrous mineral assemblage and well-rounded texture of the ooids suggests prodeltaicto estuarine with shallow marine environment reduced clastic input.